Modified silicon-carbon negative electrode material and preparation method and application thereof

Through the preparation method of modified silicon carbon negative electrode material, the problem of volume expansion of silicon carbon negative electrode material during charging and discharging is solved, and a material with a uniform pore structure is formed, which improves the stability and electrochemical performance of the electrode structure and extends the cycle life of lithium-ion batteries.

CN119707535APending Publication Date: 2025-03-28HENAN SILANE TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003967.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-carbon anode materials during charging and discharging leads to damage to the electrode structure, and the utilization rate of silicon is low and the electrical performance is not ideal.

Method used

The preparation method of modified silicon-carbon negative electrode material includes preparing porous silicon carbide, modifying porous silicon carbide, performing silicon deposition and carbon source gas deposition reaction in a fluidized bed reactor to form a modified silicon-carbon negative electrode material with a uniform pore structure.

Benefits of technology

The modified silicon carbon anode material effectively buffers the volume changes of silicon, improves the stability and electrochemical performance of the electrode structure, extends the cycle life of lithium-ion batteries, and improves the battery's energy storage capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a modified silicon-carbon negative electrode material as well as a preparation method and application thereof, and belongs to the technical field of preparation of negative electrode materials. The method comprises the following steps: preparing porous silicon carbide; placing in a multi-arc ion plating furnace chamber in an argon environment, and sputtering a modifier to obtain modified porous silicon carbide; placing in a fluidized bed reactor in an argon environment, introducing silicon source gas, and carrying out a deposition reaction; and introducing a carbon source gas for carbon deposition reaction, cooling to room temperature, washing and drying to obtain the modified silicon-carbon negative electrode material. The invention provides a modified silicon-carbon negative electrode material as well as a preparation method and application thereof. The modified silicon-carbon negative electrode material has a uniform pore structure, and is beneficial to buffering the volume change of silicon in the charging and discharging process, keeping the integrity of an electrode structure and reducing pulverization and falling of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode material preparation, and specifically relates to a modified silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] As a key component of new energy storage technology, lithium-ion batteries have been widely used in electric vehicles, mobile devices and other fields. However, existing commercial negative electrode materials, such as mesophase carbon microspheres and modified graphite, have the problem of low theoretical lithium storage capacity, which limits the further improvement of battery performance. In order to break through this limitation, researchers began to explore silicon-based negative electrode materials because silicon has an extremely high theoretical capacity (4200mAh / g), which is much higher than traditional graphite negative electrode materials. However, silicon undergoes a huge volume expansion (up to 300%) during the charging and discharging process. This volume change can cause the electrode material to fall off, pulverize, and even damage the electrode structure, thereby accelerating the decay of the battery capacity.

[0003] In order to solve the volume expansion problem of silicon-based negative electrode materials, attempts have been made to composite silicon with carbon materials in the hope of using the stability of carbon materials to alleviate the volume change of silicon. Despite this, the utilization rate of silicon in the current preparation process of silicon-carbon negative electrode materials is poor, and the electrical performance is not ideal. In addition, there are various methods for preparing porous silicon carbide, but these methods cannot stably control the morphology of the material. The template method, as a method for preparing porous silicon carbide, can retain the carbon skeleton structure, but it is easy to destroy the skeleton structure of the porous carbon during the preparation process, resulting in an uncontrollable pore structure.

[0004] In the production process of silicon-carbon negative electrode materials, the fluidization problem of porous carbon particles is also a technical challenge. Since porous carbon particles are extremely small and belong to Class C particles, these particles are prone to channeling and particle agglomeration during the fluidization process, leading to problems such as uneven silicon deposition, low silane utilization, and silicon accumulation on the reactor wall. Summary of the invention

[0005] The present invention aims to provide a modified silicon-carbon negative electrode material and a preparation method and application thereof. The modified silicon-carbon negative electrode material has a uniform pore structure, which helps to buffer the volume change of silicon during the charging and discharging process, maintain the integrity of the electrode structure, and reduce the pulverization and shedding of the material.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a modified silicon-carbon negative electrode material comprises the following steps: S1. preparing porous silicon carbide; S2, preparing modified porous silicon carbide: cleaning the porous silicon carbide obtained in step S1 to remove surface attachments, drying in an argon environment, cooling to room temperature, placing in a multi-arc ion plating furnace, sputtering a modifier, sputtering a small amount of modifier on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3, in an argon environment, placing the modified porous silicon carbide obtained in step S2 in a fluidized bed reactor, introducing a silicon source gas, and performing a deposition reaction to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, introduce carbon source gas to carry out carbon precipitation reaction on the silicon-carbon negative electrode material precursor obtained in step S3, cool to room temperature, wash three times with deionized water and anhydrous ethanol respectively, place in an oven at 60-80°C and dry for 6-8h to obtain a modified silicon-carbon negative electrode material.

[0007] Preferably, in step S1, the method for preparing porous silicon carbide comprises the following steps: A1. Silicon carbide powder and silicon powder are prepared into a mixed powder in a certain ratio; A2, placing the mixed powder in A1, polyvinyl alcohol and anhydrous ethanol in a ceramic ball mill, grinding and mixing, and drying to obtain dry powder; A3, the dry powder in A2 is crushed, passed through a 100-mesh sieve, placed in a stainless steel mold, and dry-pressed to obtain a green blank; A4. The green blank in A3 is loaded into a graphite mold, placed in a vacuum hot pressing sintering furnace, and hot pressed and sintered in an argon atmosphere to obtain porous silicon carbide.

[0008] Preferably, in step A1, the mass ratio of the silicon carbide powder to the silicon powder is 5-8:2-5.

[0009] Preferably, in step A1, the purity of the silicon carbide powder is 93%-98% and the average particle size is 30-90 μm, and the purity of the silicon powder is ≥98% and the average particle size is less than 1 μm.

[0010] Preferably, in step A2, the ball milling time is 5-6 hours, the ball-to-material ratio is 3:1, and the rotation speed is 200-250 r / min.

[0011] Preferably, in step A2, the drying temperature is 60-80° C., and the drying time is 8-16 hours.

[0012] Preferably, in step A3, the dry pressing pressure is 5-15 MPa, and the holding time is 3-6 min.

[0013] Preferably, in step A4, the hot pressing sintering parameters are set to a temperature of 1200-1600° C., a pressure of 25-45 MPa, and a holding time of 1-3 h.

[0014] Preferably, the sintering temperature has a heating rate of 5-10°C / min in the range of 20-500°C, a heating rate of 15-20°C / min in the range of 500-1000°C, and a heating rate of 5-10°C / min in the range of 1200°C-1600°C.

[0015] Preferably, the pressurization program is set as follows: when the temperature in the vacuum hot pressing sintering furnace reaches a predetermined temperature, the pressurization program is started to gradually increase the pressure, and the maximum pressure of 25-45Mpa is reached after 3-10 minutes. After maintaining the pressure for 1-3 hours, the pressure is released, and the pressure drops to 0 MPa after 30-40 minutes. After the temperature in the furnace is cooled to room temperature, the sample is taken out to obtain porous silicon carbide.

[0016] Preferably, in step S2, the modifier includes one of Sn, Li, Mg, P or Ge.

[0017] Preferably, in step S2, the drying temperature is 60-80°C and the drying time is 6-8h.

[0018] Preferably, in step S2, the sputtering modifier is specifically: 80-100 sccm argon is introduced to keep the gas pressure in the furnace at 0.35-0.5 Pa, the target power supply is turned on, the deposition current is set to 80-90 A, the bias voltage is -120 V, and the sputtering deposition is performed for 2.5-4 min.

[0019] Preferably, in step S3, the silicon source gas is one of silane, dichlorosilane, silicon tetrafluoride, and disilane.

[0020] Preferably, in step S3, the flow rate of the silicon source gas is 2-6 L / min, the deposition reaction temperature is 500-850° C., and the reaction time is 60-180 min.

[0021] Preferably, in step S4, the carbon source includes one of methane, ethane, acetylene, propane, propylene and acetone.

[0022] Preferably, in step S4, the carbon source gas flow rate is 2-5 L / min, the carbon deposition temperature is 600-800° C., and the reaction time is 120-240 min.

[0023] The present invention also provides a modified silicon-carbon negative electrode material prepared by the preparation method.

[0024] The present invention also provides a modified silicon-carbon negative electrode material prepared by the preparation method or the use of the modified silicon-carbon negative electrode material in a lithium ion battery.

[0025] The present invention also provides a lithium ion battery, comprising the modified silicon-carbon negative electrode material prepared by the preparation method or the modified silicon-carbon negative electrode material.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The present invention discloses a modified silicon-carbon negative electrode material and its preparation method and application, which effectively improves the interface bonding between silicon and carbon, increases the utilization rate of silicon and the structural stability of the electrode material, thereby reducing the volume expansion and stress during the charge and discharge process and extending the cycle life of the battery.

[0027] (2) The modified silicon-carbon negative electrode material of the present invention has higher electrical conductivity and lithium ion diffusion rate, thereby improving the charge and discharge efficiency and rate performance of the battery.

[0028] (3) The modified silicon-carbon negative electrode material of the present invention has a uniform pore structure, which helps to buffer the volume change of silicon during the charging and discharging process, maintain the integrity of the electrode structure, reduce the pulverization and shedding of the material, and provide a higher energy density. Compared with traditional graphite negative electrode materials, it can significantly improve the energy storage capacity of lithium-ion batteries.

[0029] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further illustrated by the following embodiments.

[0031] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0032] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.

[0033] Example 1 This example provides a method for preparing porous silicon carbide, comprising the following steps: A1. Prepare a mixed powder by mixing 5 g of silicon carbide powder (purity of 95%, average particle size of 60 μm) and 2 g of silicon powder (purity of 98%, average particle size of 1 μm); A2, the mixed powder in A1, 3 mL of polyvinyl alcohol and 1.5 mL of anhydrous ethanol were placed in a ceramic ball mill, wherein the ball-to-material ratio was 3:1, ball milled at 200 r / min for 6 h, ground and mixed, and dried at 80° C. for 8 h to obtain a dry powder; A3, the dry powder in A2 is crushed, passed through a 100-mesh sieve, placed in a stainless steel mold, and dry-pressed at a pressure of 15 MPa for 3 minutes to obtain a green blank; A4. Load the green blank in A3 into a graphite mold, place it in a vacuum hot pressing sintering furnace, and hot press sinter it at 1600°C in an argon atmosphere, wherein the heating rate in the range of 20-500°C is 10°C / min, the heating rate in the range of 500-1000°C is 20°C / min, and the heating rate in the range of 1200°C-1600°C is 5°C / min. Keep it warm for 2 hours. When the temperature in the furnace reaches 1300°C, start the pressurization program and begin to gradually pressurize. After 7 minutes, the maximum pressure of 25 MPa is reached. After keeping warm for 2 hours, start to release the pressure. After 40 minutes, the pressure drops to 0 MPa. After the temperature in the furnace cools to room temperature, take out the sample to obtain porous silicon carbide.

[0034] Example 2 This example provides a modified silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Preparation of porous silicon carbide: the same preparation method as in Example 1; S2, preparing modified porous silicon carbide: the porous silicon carbide obtained in step S1 is ultrasonically cleaned with deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface attachments, dried at 80°C for 6 hours in an argon environment, cooled to room temperature, placed in a multi-arc ion plating furnace, and 80 sccm of argon is introduced to keep the pressure in the furnace at 0.35 Pa, the target power supply is turned on, the deposition current is set to 90A, the bias voltage is -120V, Sn is sputtered, and the sputtering deposition is 2.5 minutes. A small amount of Sn is sputtered on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3. In an argon environment, the modified porous silicon carbide obtained in step S2 is placed in a fluidized bed reactor, silane is introduced at a gas flow rate of 2 L / min, and the modified porous silicon carbide obtained in step S2 is subjected to a deposition reaction at 600° C. for 120 min to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, ethane is introduced at a gas flow rate of 2 L / min, and the silicon-carbon negative electrode material precursor obtained in step S3 is subjected to a carbon precipitation reaction at 750°C for 180 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 8 h to obtain a modified silicon-carbon negative electrode material.

[0035] Embodiment 3 This embodiment provides a silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Preparation of porous silicon carbide: the same preparation method as in Example 1; S2, preparing modified porous silicon carbide: the porous silicon carbide obtained in step S1 is ultrasonically cleaned with deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface attachments, dried at 80°C for 6 hours in an argon environment, cooled to room temperature, placed in a multi-arc ion plating furnace, and 90 sccm of argon is introduced to keep the furnace pressure at 0.45 Pa, the target power supply is turned on, the deposition current is set to 85A, the bias voltage is -120V, Sn is sputtered, and the sputtering deposition is 3 minutes, and a small amount of Li is sputtered on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3. In an argon environment, the modified porous silicon carbide obtained in step S2 is placed in a fluidized bed reactor, disilane is introduced at a gas flow rate of 3 L / min, and the modified porous silicon carbide obtained in step S2 is subjected to a deposition reaction at 800° C. for 90 min to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, methane is introduced at a gas flow rate of 2 L / min, and the silicon-carbon negative electrode material precursor obtained in step S3 is subjected to a carbon precipitation reaction at 800°C for 150 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 8 h to obtain a modified silicon-carbon negative electrode material.

[0036] Embodiment 4 This embodiment provides a silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Preparation of porous silicon carbide: the same preparation method as in Example 1; S2, preparing modified porous silicon carbide: the porous silicon carbide obtained in step S1 is ultrasonically cleaned with deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface attachments, dried at 80°C for 6 hours in an argon environment, cooled to room temperature, placed in a multi-arc ion plating furnace, and 100 sccm of argon is introduced to keep the pressure in the furnace at 0.5 Pa, the target power supply is turned on, the deposition current is set to 80 A, the bias voltage is -120 V, Sn is sputtered, and the sputtering deposition is 3 minutes, and a small amount of P is sputtered on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3. In an argon environment, the modified porous silicon carbide obtained in step S2 is placed in a fluidized bed reactor, dihydrogen dichlorosilane is introduced at a gas flow rate of 4 L / min, and the modified porous silicon carbide obtained in step S2 is subjected to a deposition reaction at 850° C. for 60 min to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, ethane is introduced at a gas flow rate of 3 L / min, and the silicon-carbon negative electrode material precursor obtained in step S3 is subjected to a carbon precipitation reaction at 800°C for 150 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 8 h to obtain a modified silicon-carbon negative electrode material.

[0037] Comparative Example 1 The preparation method is the same as that of Example 2, except that step S2 is not performed, that is, the porous silicon carbide is not modified.

[0038] Comparative Example 2 The preparation method is the same as that of Example 3, except that step S4 is not performed.

[0039] Comparative Example 3 S1. Preparation of porous silicon carbide: the same preparation method as in Example 1; S2, preparing modified porous silicon carbide: the porous silicon carbide obtained in step S1 is ultrasonically cleaned with deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface attachments, dried at 80°C for 6 hours in an argon environment, cooled to room temperature, placed in a multi-arc ion plating furnace, and 100 sccm of argon is introduced to keep the pressure in the furnace at 0.5 Pa, the target power supply is turned on, the deposition current is set to 80 A, the bias voltage is -120 V, Sn is sputtered, and the sputtering deposition is 3 minutes, and a small amount of P is sputtered on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3. In an argon environment, the modified porous silicon carbide obtained in step S2 is placed in a fluidized bed reactor, dihydrogen dichlorosilane is introduced at a gas flow rate of 4 L / min, and the modified porous silicon carbide obtained in step S2 is subjected to a deposition reaction at 1000° C. for 50 min to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, ethane is introduced at a gas flow rate of 3 L / min, and the silicon-carbon negative electrode material precursor obtained in step S3 is subjected to carbon precipitation reaction at 950°C for 100 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 8 h to obtain a modified silicon-carbon negative electrode material.

[0040] The effects of the negative electrode materials provided in the above embodiments and comparative examples were verified by the following tests: The negative electrode materials provided in the above embodiments and comparative examples are prepared into a lithium ion battery, comprising the following steps: The button cell was assembled in a glove box (water and oxygen content were both less than 0.01 ppm).

[0041] The prepared negative electrode material was used as the negative electrode active material, and was weighed in sequence with acetylene black and polyvinylidene fluoride in a mass ratio of 8:2:1. After being fully ground in an agate mortar, an appropriate amount of N-methylpyrrolidone was added to mix into a uniform slurry. The slurry was evenly coated on a copper foil using an infrared drying coater and dried at 120°C for 45 minutes to obtain a dry electrode sheet. The dry electrode sheet was rolled and cut by a roller press to obtain a negative electrode sheet with a diameter of 12 nm. The negative electrode active material loading of each negative electrode sheet was 0.9 mg cm -2. The positive electrode uses a metal lithium sheet (diameter 12 mm, thickness 0.5 mm), the separator is glass fiber (Whatman, 20 mm), and the electrolyte is 1 M LiPF6 (dissolved in a mixed solvent of EC:DMC = 1:1). The negative electrode sheet, electrolyte, separator, electrolyte and metal lithium sheet are assembled in this order, and then sealed with a hydraulic sealing machine to obtain a lithium-ion battery for charge and discharge tests. The voltage range is 5mV-1.5V and the current density is 80mA / g. The performance parameters of the lithium-ion battery obtained are tested, such as the charge and discharge capacity, cycle performance, and first efficiency. The results are shown in Table 1.

[0042] Table 1 Electrochemical properties of lithium-ion batteries

[0043] As can be seen from Table 1, the first reversible capacity of Examples 2, 3, and 4 is higher than that of Comparative Examples 1, 2, and 3. Among them, the first reversible capacity of Example 2 is the highest, reaching 1680.5 mAh / g, while the capacity of Comparative Example 1 is the lowest, which is 1359.1 mAh / g. The first efficiency of all examples is higher than 90%, indicating that these negative electrode materials have high initial charge and discharge efficiency. Among them, the first efficiency of Example 2 is the highest, which is 91.16%, while the efficiency of Comparative Example 1 is the lowest, which is 87.83%. The charge and discharge capacity retention rates of Examples 2, 3, and 4 after 500 cycles are all higher than 90%, showing good cycle stability. Among them, the capacity retention rate of Example 2 is the highest, which is 92.67%, while the capacity retention rate of Comparative Example 1 is the lowest, which is 88.89%.

[0044] Compared with Comparative Examples 1-3 (unmodified or partially modified negative electrode materials), Examples 2-4 have higher first reversible capacity and cycle stability, which indicates that the modification step, especially the sputtering modifier in step S2, effectively improves the electrochemical performance of the negative electrode material.

[0045] Examples 2-4 used different modifiers (Sn, Li, P), but all had better performance than the comparative example. This shows that different modifiers have a positive effect on improving the performance of negative electrode materials, but the specific effect may vary depending on the type of modifier and sputtering conditions.

[0046] The cycle stability of Examples 2-4 is generally better than that of the comparative example, which is related to the uniform pore structure of the modified silicon-carbon negative electrode material. This structure helps to buffer the volume change of silicon during the charge and discharge process, reduce the pulverization and shedding of the material, and thus improve the cycle life of the battery.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a modified silicon-carbon negative electrode material, characterized in that: The steps include: S1. preparing porous silicon carbide; S2, preparing modified porous silicon carbide: cleaning the porous silicon carbide obtained in step S1 to remove surface attachments, drying in an argon environment, cooling to room temperature, placing in a multi-arc ion plating furnace, sputtering a modifier, sputtering a small amount of modifier on the surface of the porous silicon carbide to obtain modified porous silicon carbide; S3, in an argon environment, placing the modified porous silicon carbide obtained in step S2 in a fluidized bed reactor, introducing a silicon source gas, and performing a deposition reaction to obtain a silicon-carbon negative electrode material precursor; S4. In an argon environment, introduce carbon source gas to carry out carbon precipitation reaction on the silicon-carbon negative electrode material precursor obtained in step S3, cool to room temperature, wash three times with deionized water and anhydrous ethanol respectively, place in an oven at 60-80°C and dry for 6-8h to obtain a modified silicon-carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing porous silicon carbide comprises the following steps: A1. Silicon carbide powder and silicon powder are prepared into a mixed powder in a certain ratio; A2, placing the mixed powder in A1, polyvinyl alcohol and anhydrous ethanol in a ceramic ball mill, grinding and mixing, and drying to obtain dry powder; A3, the dry powder in A2 is crushed, passed through a 100-mesh sieve, placed in a stainless steel mold, and dry-pressed to obtain a green blank; A4. The green blank in A3 is loaded into a graphite mold, placed in a vacuum hot pressing sintering furnace, and hot pressed and sintered in an argon atmosphere to obtain porous silicon carbide.

3. The preparation method according to claim 2, characterized in that: In step A4, the hot pressing sintering parameters are set as temperature 1200-1600° C., pressure 25-45 MPa, and holding time 1-3 h.

4. The preparation method according to claim 1, characterized in that: In step S2, the modifier includes one of Sn, Li, Mg, P or Ge.

5. The preparation method according to claim 1, characterized in that: In step S2, the sputtering modifier is specifically: 80-100 sccm argon is introduced to keep the gas pressure in the furnace at 0.35-0.5 Pa, the target power is turned on, the deposition current is set to 80-90 A, the bias voltage is -120 V, and the sputtering deposition is performed for 2.5-4 min.

6. The preparation method according to claim 1, characterized in that: In step S3, the flow rate of the silicon source gas is 2-6 L / min, the deposition reaction temperature is 500-850° C., and the reaction time is 60-180 min.

7. The preparation method according to claim 1, characterized in that: In step S4, the carbon source gas flow rate is 2-5 L / min, the carbon deposition temperature is 600-800° C., and the reaction time is 120-240 min.

8. The modified silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the modified silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or the modified silicon-carbon negative electrode material according to claim 8 in lithium-ion batteries.

10. A lithium ion battery, characterized in that: The modified silicon-carbon negative electrode material is prepared by the preparation method described in any one of claims 1 to 7 or the modified silicon-carbon negative electrode material described in claim 8.